The Nexus between Electricity Consumption and Economic Growth: New Insights from Meta-Analysis - BOUOIYOUR, Jamal; SELMI, Refk; OZTURK, Ilhan (International Journal of Energy Economics and Policy, 2014)
Although many factors have been identified to explain the nexus between electricity consumption and economic growth, the empirical evidence is rather mixed. Given these contradictory conclusions, the aim of this paper is to find out which outcome the meta-analysis would support by applying meta-analysis to a sample of the empirical results of 43 studies published between 1996 and 2013. We found that the conservation hypothesis is widely associated to American and European countries. However, conservative policies are likely to have an adverse effect on the economic growth in Asian and MENA countries. Conversely to expectations, the growth hypothesis is heavily associated to studied countries and considered modeling specifications. Additionally, while a neutrality hypothesis is insignificantly associated to MENA countries, the feedback hypothesis is not supported when appealing a panel of American economies. Therefore, the inconclusive results may be mainly due to the different country samples, econometric methodologies and to the fact that energy policies cannot be designed without considering economic and environmental factors, which are unfortunately excluded in the majority of studies. Further analysis should focus more on the new approaches rather than usual methods based on a set of common variables for different countries. Keywords: electricity consumption; economic growth; meta-analysis. JEL Classifications: C2; Q43